Comparative electrophysiological techniques in the diagnosis of carpal tunnel syndrome in patients with diabetic polyneuropathy - AKYÜZ, GÜLSEREN DERYA; YAĞCI, İLKER; GÜNDÜZ, OSMAN HAKAN (ELSEVIER IRELAND LTD, 2010)
Objective: To determine utility of comparative electrophysiological techniques in differentiating carpal tunnel syndrome (CTS) in the background of diabetic polyneuropathy (DPN). Design: Ninety diabetic patients were classified into three groups: normal, CTS, and DPN according to nerve conduction studies (NCSs). The patients in the DPN group were divided into two subgroups of DPN and DPN-CTS according to clinical criteria. The comparative electrophysiological parameters including median-radial sensory distal latency difference (M-RSLD), median-ulnar sensory distal latency difference (M-USLD) and lumbrical-interosseous median-ulnar distal latency difference (LIMULD) were compared in subgroups of DPN, DPN-CTS and CTS. Results: Thirty-five (38.8%), 47(52.3%), and 8(8.9%) patients were diagnosed as CTS, DPN, and normal, respectively, according to NCS. After clinical stratification, 25 patients were diagnosed as DPN and 22 patients were diagnosed as DPN-CTS. The mean M-USLD and LIMULD values were similar in CTS and DPN-CTS groups, but larger than DPN statistically (p < 0.05 for all). LIMULD, M-RSLD and M-USLD were positive in 88.4, 73 and 54% in the DPN-CTS group, respectively. Conclusions: Electrophysiological abnormalities were common in diabetic patients and LIMULD can identify CTS in diabetic DPN patients better than M-RSLD and M-USLD. (C) 2010 Elsevier Ireland Ltd. All rights reserved.
Keywords: Diabetes mellitus; Carpal tunnel syndrome; Polyneuropathy; Electrodiagnosis; MEDIAN MONONEUROPATHY; NEUROPATHY; SEVERITY; MELLITUS